Features of Life Planning Among Student Youth During Wartime and the Post-Pandemic Period - Pomytkina , Liubov; Melnyk , Nataliia; Kovtun , Olena; Kokarieva , Anzhelika (Insight: the psychological dimensions of society, 2024)
The article presents the findings of a theoretical and empirical study on the peculiarities of life planning among student youth during wartime and the post-pandemic period. The authors conceptualize life planning as the capacity of individuals to integrate personal experiences, maintain an awareness of the present, develop a realistic vision of the future, exhibit tolerance for uncertainty, and authentically experience the passage of time and its associated values and meanings in the context of executing personal life projects. The purpose of the publication is to highlight the results of a study of the features of life planning of student youth during martial law in the post-pandemic period. Methods. The study utilized the following instruments: the “Balanced Time Perspective Scale” (Zimbardo & Boyd, 1999), the “Diagnosis of Personal Time Disorganizers” (Nestorenko & Mikos, 2020), the “Subjective Alienation Questionnaire” (Maddi, 2004), and the “Uncertainty Tolerance Questionnaire” (Budner, 1962), along with statistical methods including the Mann-Whitney U-test and Student’s t-test. Results indicate that students’ ability to plan their lives effectively is associated with accurate time orientation, a low level (or absence) of personal time disorganizers, an authentic attitude towards themselves and others (as evidenced by a low level of alienation), and tolerance for uncertainty. Most students exhibit characteristics of an unbalanced time perspective, with a predominant focus on the present due to their experiences of extreme living conditions, and they tend to plan for the future only in the short term. Discussion and conclusions. The characteristics of life planning among students include competence in time management, which encompasses an optimal attitude towards the past, present, and future, flexible and deliberate organization of time, and accountability for decisions and plans; and authentic life perception, particularly among students with a balanced time perspective. Conversely, students with an unbalanced time perspective exhibit greater time disorganization and intolerance of uncertainty, which indicates difficulties in comprehending their own goals and intentions and a limited outlook on the future. These issues are linked to the current experiences of young people related to the ongoing war and the post-pandemic context.